An examination of Homo naledi early juveniles recovered from the Rising Star cave system, South Africa - Juliet K. Brophy; Debra R. Bolter; Marina Elliott; John Hawks; Lee R. Berger (Taylor & Francis Group, 2024)
AbstractBackground Six Homo naledi early juveniles were recovered from U.W. 101 (Dinaledi Chamber), U.W. 102 (Lesedi Chamber), and U.W. 110 in the Rising Star cave system.Aim This paper develops the information for the H. naledi early juvenile life stage, as defined by a combination of deciduous and permanent dentition, and the eruption of the first permanent molar.Subjects and methods The growing number of young individuals recovered from the Rising Star cave system allows us to gain a better understanding of their variation, or lack thereof, and provides a basis to estimate broad ranges for age at death of the individuals. The individuals are identified and described through craniodental remains and spatial associations.Results and conclusion Our results show that the teeth are remarkably consistent across the localities in their metric and non-metric traits, and our analyses refine previous estimations on dental eruptions with the first permanent molar erupting first in the sequence among permanent teeth.